Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Scaffolding Untuk Meningkatkan Motivasi Belajar Siswa Pada Pelajaran Pendidikan Pancasila SD - Restika, Heni; Maritasari, Donna Boedi; Rohini, Rohini (Mataram University, 2025)
The teacher-centered learning process, which does not utilize engaging learning methods or media, contributes to the lack of motivation among fourth-grade students at SDN 1 Ketangga in Pancasila Education. This study aims to develop scaffolding-based Student Worksheets (LKPD) to improve student learning motivation in Pancasila Education, focusing on the aspects of perseverance in learning, resilience in the face of difficulties, interest, achievement, and independence in learning. This study uses the ADDIE development model, which includes five stages: Analysis, Development, Design, Implementation, and Evaluation. The data collection instruments used were questionnaires validated by material experts, validated by media experts, and questionnaires assessing student learning motivation. The media expert validation results achieved a score of 75, within the range of 61.3–75.6, categorized as